PENGARUH KONFLIK PERAN DAN KECERDASAN EMOSIONAL TERHADAP KEPUASAN KERJA GURU SEKOLAH LUAR BIASA NEGERI PEMBINA PROVINSI RIAU - Kurnia, Fajar; -, Marzolina; Pramadewi, Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to analyze the influence of role conflict and emotional intelligence on job satisfaction of teachers. The experiment was conducted on teacher Special School Pembina of Riau Province. The population in this study is a teacher Special School Pembina of Riau Province. The samples were 35 respondents in this study. Indipendent variables in this research is role conflict and emotional intelligence as dependent variable is teacher’s job satisfaction. This study using Multiple Linier Regression Analysis as a method, with using SPSS version 18. Simultanous regression (F test) showed the independent variables had a significant influences on the dependent variable (Job Satisfaction). The magnitude of influence independent variables was 70,8% and the remaining 29,5% was influenced by other variables.The result of this research showed that role conflict and emotional intelligent had significant influence on teacher’s job satisfaction. Partially, role conflict have negative significant influence to teacher’s job satisfaction, while emotional intelligence on teacher’s job satisfaction in positive significant.  Keywords: Role Conflict, Emotional Intelligance and Job Satisfaction